2023
DOI: 10.21203/rs.3.rs-2750900/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the trade-off between speed and efficiency in undulatory swimming using a bio-inspired robot

Abstract: Anguilliform swimmers, like eels or lampreys, are highly efficient swimmers. Key to understanding their performances is the relationship between the body's kinematics and resulting swimming speed and efficiency. But, we cannot prescribe kinematics to living fish, and it is challenging to measure their power consumption. Here, we characterise the swimming speed and cost of transport of a free-swimming undulatory bio-inspired robot as we vary its kinematic parameters, including joint amplitude, body wavelength, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 57 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The kinematics analysis of fish swimming using the traveling wave is a hot topic in the fields of swimming dynamics and fluid mechanics [55][56][57]. In the field of bionic robotic fish, scholars have experimentally observed that robotic fish performs better [21][22][23]58,59] when the traveling wave is the dominant component of the fish body wave. However, it is challenging to analyze the traveling wave and standing wave.…”
Section: The Complex Orthogonal Decomposition Methods Of Fish Body Wavementioning
confidence: 99%
See 2 more Smart Citations
“…The kinematics analysis of fish swimming using the traveling wave is a hot topic in the fields of swimming dynamics and fluid mechanics [55][56][57]. In the field of bionic robotic fish, scholars have experimentally observed that robotic fish performs better [21][22][23]58,59] when the traveling wave is the dominant component of the fish body wave. However, it is challenging to analyze the traveling wave and standing wave.…”
Section: The Complex Orthogonal Decomposition Methods Of Fish Body Wavementioning
confidence: 99%
“…In the case of a low traveling index, the predominant motion is the standing wave, which displaces the surrounding fluid laterally. Its momentum flux typically occurs in the lateral direction, potentially impacting swimming efficiency [23]. Furthermore, Anastasiadis and Ijspeert et al [23] pointed out that a higher traveling index can reduce the cost of transport (COT) of robotic fish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation